A case report of moyamoya disease in children treated with encephalo-duro-myo-arterio-pericranial synangiosis (Medical Journal of Indonesia, 2021)
Moyamoya disease that manifests during childhood may pose a special challenge for surgeons. We report a case of a 10-year-old girl who suffered from moyamoya disease and was successfully treated with encephalo-duro-myo-arterio-pericranial synangiosis (EDMAPS). She presented with a recurrent transient ischemic attack that worsened for 1 year. She was aphasic globally (sensory and motor) and had slightly weak right extremities. Her magnetic resonance angiography and computed tomography angiography showed the typical features of moyamoya disease with bilateral stenosis at the terminal internal carotid artery, bilaterally abnormal vascular networks, and a left ischemic event involving the temporoparietal region. She was recovered well after underwent bilateral EDMAPS, fully regained her language function after 3 months, and gathered her strength back. Therefore, EDMAPS could be a good, safe, and effective treatment for moyamoya disease in children.